Ictus Emeticus and Nondominant Temporal Lobe - J Gordon Millichap (Pediatric Neurology Briefs)
Two patients, aged 18 and 47 years, with ictal vomiting during temporal lobe seizures documented with bilateral depth electrodes are reported from the Department of Neurology, New York School of Medicine, Hospital for Joint Diseases, New York.